Quantifying Degradative Loss of Terrigenous OrganicCarbon in Surface Sediments Across the Laptevand East Siberian Sea; Global Biogeochemical Cycles; Vol. 33, iss. 1 - Broder L. Lisa; Andersson A. August; Tesi T. Tommaso; Semiletov I. P. Igor Petrovich; Gustafsson O. Orjan (2019, 2019)
Title screen